2016
DOI: 10.1016/j.jclepro.2016.06.123
|View full text |Cite
|
Sign up to set email alerts
|

Steering innovations towards a green economy: Understanding government intervention

Abstract: In this paper we analyse institutional conditions facilitating the transition towards a green economy by encouraging investment in the enhancement of natural capital and social equity, focusing especially on government interventions. Presenting a conceptual institutional model how innovation generally occurs, we depict system levels that can be influenced by government interventions to facilitate societal innovations towards a green economy. We hypothesize that the transition to a green economy is about extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 38 publications
(51 reference statements)
0
48
0
Order By: Relevance
“…Results indicated that government intervention may result in adverse effects on profits and social welfare. Besides, Droste et al [39] investigated institutional conditions facilitating the transition towards a green economy of government intervention. Madani and Rasti-Barzoki [40] considered the role of government and interactions between the government and supply chain members' decisions.…”
Section: Governmental Interventionmentioning
confidence: 99%
“…Results indicated that government intervention may result in adverse effects on profits and social welfare. Besides, Droste et al [39] investigated institutional conditions facilitating the transition towards a green economy of government intervention. Madani and Rasti-Barzoki [40] considered the role of government and interactions between the government and supply chain members' decisions.…”
Section: Governmental Interventionmentioning
confidence: 99%
“…Green innovations are crucial components to support the transition to a green economy (Droste et al, ), allowing firms to respond to conflicting demands coming from several stakeholders. Earlier research supports the existence of three driving forces of green innovation development (Albino, Balice, Dangelico, & Iacobone, ; Chen, ; Doran & Ryan, ; Horbach, Rammer, & Rennings, ; Vachon & Klassen, ): (i) consumers increasing environmental awareness; (ii) stricter environmental regulations; and (iii) fierce competition among peers, suggesting the existence of a positive relationship between these factors and the green innovation performance (GIP) of firms.…”
Section: Introductionmentioning
confidence: 99%
“…Green innovations are crucial components to support the transition to a green economy (Droste et al, 2016), allowing firms to respond to conflicting demands coming from several stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…According to Lindman, Söderholm (2016), the green economy policy discourse recognizes the importance of actively promoting investments in new technologies that can open up the energy sector from the incumbent and typically less sustainable technologies based on fossil fuels and other energy resources that are non-renewable. According to Droste et al (2016) any economic strategy will require investments, but the normative green economy vision needs both private and public investment to be steered towards greener and fairer strategies. It is therefore recognized that such investments have to be "supported by targeted public expenditure, policy reforms, and regulation changes" (UNEP, 2011, p. 16) which stresses the role of government intervention.…”
Section: Theoretical Provisions Of the Importance Of The Green Technomentioning
confidence: 99%